The Effectiveness of H5P-Asisted Differentiated-Independent Learning Model to Increase Low-Ability Students' Scientific Literacy - Indrawati Wilujeng; Trise Nurul Ain; Adhy Putri Rilianti; Faiz Hasyim; Maskanatul Fiqiyah (Universitas Negeri Semarang, 2025)
Scientific literacy is a critical skill in the era of Smart Society 5.0. Recent studies show that 76.9% of students are in the lowest category, the nominal level, in terms of science literacy. This prompted the researchers to examine the effectiveness of the H5P-assisted Differentiated-Independent Learning model in enhancing the scientific literacy of low-ability students. The state of the art in this research is demonstrated through a review of previous studies that explored the implementation of innovative learning models to promote scientific literacy. However, these models either fail to integrate the use of technology with pedagogical approaches or do not specifically address students with low ability. Therefore, the novelty of this study lies in the integration of H5P learning media as a technological resource, alongside a targeted focus on lower ability students as the primary research subjects. This study employed an experimental method with a one-group pretest-posttest design, including a replication class. The study revealed that the H5P-assisted Differentiated-Independent model was effective, as indicated by an average n-gain score of 0.74, which falls within the high category. The paired t-test demonstrated a significant difference between the pretest and posttest scores across all classes. Furthermore, the independent t-test indicated a consistent increase in scientific literacy skills in all classes, with 83% of students responding very positively based on the questionnaire. In summary, the H5P-assisted Differentiated-Independent model has a positive impact on enhancing the scientific literacy skills of low-ability students.